2013
DOI: 10.1021/cs400231f
|View full text |Cite
|
Sign up to set email alerts
|

PtII-Catalyzed Ethylene Hydrophenylation: Influence of Dipyridyl Chelate Ring Size on Catalyst Activity and Longevity

Abstract: Expansion of the dipyridyl ligand from a fiveto six-membered chelate for Pt II -catalyzed ethylene hydrophenylation provides an enhancement of catalyst activity and longevity. Mechanistic studies of [(dpm)Pt(Ph)(THF)]-[BAr′ 4 ] [dpm = 2,2′-dipyridylmethane, and Ar′ = 3,5-(CF 3 ) 2 C 6 H 3 ] attribute the improved catalytic performance at elevated temperatures to a favorable change in entropy of activation with an increase in chelate ring size. The Pt II catalyst precursor [(dpm)Pt(Ph)(THF)][BAr′ 4 ] is among t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
45
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 47 publications
(53 citation statements)
references
References 26 publications
5
45
0
Order By: Relevance
“…Catalysts based on Ru, Ir, and Pt have been reported for olefin hydroarylation using hydrocarbons (e.g., benzene and ethylene) , , . In an effort to systematically probe the influence of donor ability and sterics of ancillary ligands on catalytic olefin hydroarylation, we have studied ethylene hydrophenylation using [(Xp)Ru(L)(NCMe)Ph] n + {Xp = Tp ( n = 0) or PPA ( n = 1); L = neutral, 2e – donor ligand} catalyst precursors , , , .…”
Section: Catalytic C–h Bond Functionalization: Olefin Hydroarylationmentioning
confidence: 99%
“…Catalysts based on Ru, Ir, and Pt have been reported for olefin hydroarylation using hydrocarbons (e.g., benzene and ethylene) , , . In an effort to systematically probe the influence of donor ability and sterics of ancillary ligands on catalytic olefin hydroarylation, we have studied ethylene hydrophenylation using [(Xp)Ru(L)(NCMe)Ph] n + {Xp = Tp ( n = 0) or PPA ( n = 1); L = neutral, 2e – donor ligand} catalyst precursors , , , .…”
Section: Catalytic C–h Bond Functionalization: Olefin Hydroarylationmentioning
confidence: 99%
“…Previous work has shown these conditions to be optimal for related Pt(II) catalysts. [23][24][25] Under these conditions, catalyst precursors with bisphosphine ligands (complexes 1-6) showed < 0.1 equivalents of ethylbenzene. Styrene was the dominant product for all of the catalyst precursors 1-6.…”
Section: Resultsmentioning
confidence: 98%
“…[13][14][15][16][17][18][19][20][21][22] Our group has been studying Pt(II) complexes of the type [(N~N)Pt(THF)(Ph)][BAr' 4 ] (N~N = bis-chelating dipyridyl ligand, Ar' = 3,5-bis(trifluoromethyl)phenyl), which have been found to be active catalysts for ethylene hydrophenylation to yield ethylbenzene. 4,[23][24][25][26][27][28] In addition to ethylbenzene, the formation of styrene is typically observed when using these Pt(II) complexes as catalysts. For the [(N~N)Pt(THF)(Ph)][BAr' 4 ] catalysts, the formation of styrene is proposed to occur via β-hydride elimination from [(N~N)Pt(CH 2 CH 2 Ph)] + intermediates followed by styrene dissociation.…”
Section: Introductionmentioning
confidence: 99%
“…A further step to improve the longevity of the catalyst was made by changing the bipy-type ligands by dipyridyls, such as 2,2-dipyridylmethane (dpm) (Scheme 6). 23 Bipy and dpm have rather close electronic properties, but different steric properties. It has been shown that complexes of type 3 bearing a dpm ligand (E = CH 2 , R = H in Scheme 6) are about 5.6 times more active than t Bubipy systems of type 2 under the same reaction conditions (Scheme 3).…”
Section: Hydroarylation Of C-c Multiple Bondsmentioning
confidence: 99%